Masterpieces of the imaginative mind. literature's most fantastic works - Rabkin, Eric S.; Teaching Company (Chantilly, VA : Teaching Co., 2007)
University of Michigan professor Eric S. Rabkin discusses the fantastic in its most important modern variety, science fiction, as part of the entire course on fantasy literature.
Part 1: Disc 1. lecture 1. The Brothers Grimm & fairy tale psychology -- lecture 2. Propp, structure, and cultural identity -- lecture 3. Hoffman and the theory of the fantastic -- lecture 4. Poe : genres and degrees of the fantastic -- lecture 5. Lewis Carroll : puzzles, language, & audience -- lecture 6. H.G. Wells : we are all talking animals ; Disc 2. lecture 7. Franz Kafka : dashed fantasies -- lecture 8. Woolf : fantastic feminism & periods of art -- lecture 9. Robbe-Grillet : experimental fiction & myth -- lecture 10. Tolkien & mass production of the fantastic -- lecture 11. Children's literature and the fantastic -- lecture 12. Postmodernism and the fantastic ; Part 2: Disc 3. lecture 13. Defining science fiction -- lecture 14. Mary Shelley : grandmother of science fiction -- lecture 15. Hawthorne, Poe, and the Eden complex -- lecture 16. Jules Verne and the Robinsonade -- lecture 17. Wells : industrialization of the fantastic -- lecture 18. The history of utopia ; Disc 4. lecture 19. Science fiction and religion -- lecture 20. Pulp fiction, Bradbury, & the American myth -- lecture 21. Robert A. Heinlein : he mapped the future -- lecture 22. Asimov and Clarke : cousins in utopia -- lecture 23. Ursula K. Le Guin : transhuman anthropologist -- lecture 24. Cyberpunk, postmodernism, and beyond.
"Literature & English language"--Container insert.
Includes bibliographical references (p. 64-71) in accompanying guidebook.
DVD.
Lecturer: Eric S. Rabkin, University of Michigan.
Keywords: Fantasy fiction -- History and criticism; Fantasy literature -- History and criticism; Science fiction -- History and criticism; Fantasy fiction -- History and criticism -- Videorecordings; Fantasy literature -- History and criticism -- Videorecordings; Science fiction -- History and criticism -- Videorecordings; DVD videodiscs